The Analysis of Production Performance and Economic Efficiency of Broiler Farming in Sragen Regency, Indonesia - Budiarto, Imam; Wahyu Mulyono, Ali Mursyid; Sariri, Ahimsa Kandi; Husein, Muhammad; Qui, Nguyen Hoang (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aims to determine the production performance and income analysis of the broiler livestock business in Sragen Regency, Central Java Province, in 2024. The study used a survey method with two broiler chicken farmers who served as respondents. The data used comes from observations and direct interviews with farmers. The observed variables include production performance (feed consumption, body weight, FCR, depletion or mortality) and farming business (fixed costs, variable costs, total costs, revenue, and sales). The data analysis method used is the descriptive method. Feed consumption produced at Chicken Park Farm is higher than UD Sri Mulyo Farm with a difference of 0.29 kg/head, but the difference in broiler body weight is 0.08 kg/head, and the difference in Feed Convention Ratio (FCR) obtained by UD Sri Mulyo Farm is higher than Chicken Park Farm, both with a difference of 0.08 kg/head. Meanwhile, the depletion or mortality between the two broiler farms is the same at 2.4%. The income obtained in the broiler farming business at Chicken Park farm, with a population of 4.000 birds, is higher than the 3.000 broiler population at UD Sri Mulyo Farm, with a difference of Rp. 2.016 / head, -